2013
DOI: 10.1016/j.jtcvs.2013.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Conventional surgery, sutureless valves, and transapical aortic valve replacement: What is the best option for patients with aortic valve stenosis? A multicenter, propensity-matched analysis

Abstract: SAVR was associated with lower 30-day mortality than TA-TAVR. SAVR was also associated with a lower risk of postoperative aortic regurgitation compared with TA-TAVR. We did not find other significant differences in outcomes among matched patients treated with SAVR, SU-AVR, and TA-TAVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 21 publications
1
75
1
Order By: Relevance
“…A recent systematic review and meta-analysis on 12 studies using Perceval Sutureless valve, Medtronic 3F Enable, or EDWARDS INTUITY confirmed that sutureless aortic valve implantation is a safe procedure associated with shorter cross-clamp and cardiopulmonary bypass time compared to conventional approaches 21. Sutureless and rapid deployment aortic valve replacement, furthermore, was associated with lower 30-day mortality and lower risk of postoperative aortic regurgitation compared to transapical TAVI in a multicenter, propensity-matched analysis22 and improved survival up to 24 months23 compared to TAVI, respectively. Compared to the implantation of stented valves, the use of Perceval sutureless valve in retrospective analyses resulted in shorter procedural times24 associated with better clinical outcomes as measured by blood transfusions, shorter intensive care unit stay, ventilation time, postoperative atrial fibrillation, pleural effusions, respectively, and reduced hospital costs by approximately 25% 25…”
mentioning
confidence: 98%
“…A recent systematic review and meta-analysis on 12 studies using Perceval Sutureless valve, Medtronic 3F Enable, or EDWARDS INTUITY confirmed that sutureless aortic valve implantation is a safe procedure associated with shorter cross-clamp and cardiopulmonary bypass time compared to conventional approaches 21. Sutureless and rapid deployment aortic valve replacement, furthermore, was associated with lower 30-day mortality and lower risk of postoperative aortic regurgitation compared to transapical TAVI in a multicenter, propensity-matched analysis22 and improved survival up to 24 months23 compared to TAVI, respectively. Compared to the implantation of stented valves, the use of Perceval sutureless valve in retrospective analyses resulted in shorter procedural times24 associated with better clinical outcomes as measured by blood transfusions, shorter intensive care unit stay, ventilation time, postoperative atrial fibrillation, pleural effusions, respectively, and reduced hospital costs by approximately 25% 25…”
mentioning
confidence: 98%
“…Transcatheter technology has been intensively studied since 2002 and has evolved now into a new sutureless surgical prosthesis idea. Sutureless alternative to the conventional (sutured) biological valves has been in clinical use since 2008 [9][10][11][12], and has been associated with good clinical and hemodynamic outcomes [13][14][15][16][17][18][19][20]. Excellent outcomes have been demonstrated with sutureless AVR in minimally invasive surgical setting [21][22][23][24], however without direct comparison with conventional prostheses.…”
mentioning
confidence: 99%
“…Recent studies comparing TAVI with sutureless prostheses highlight the higher rate of periprosthetic leakage in the TAVI group, along with a higher mortality rate in the transcatheter group. 8,9 We recommend the sutureless aortic prosthesis as the first choice of treatment for patients with a high surgical risk within the intermediate or grey area between TAVI and conventional surgery.…”
Section: Discussionmentioning
confidence: 99%